Issues in the interpretation of the EU legislation on the example of a contract for the supply of agricultural produce - Okurowska, Aneta (Przegląd Prawa Rolnego, 2023)
The purpose of the deliberations was to determine whether, under the provisions of European Union law, the clause on termination or cancellation of a contract is a mandatory element of the contract for the supply of agricultural produce. The considerations were carried out pursuant to the canons of interpretation of EU law. While a grammatical interpretation, taking into account the official languages of the European Union, did not lead to a conclusive answer, extra-linguistic methods of interpretation have resulted in surprising conclusions, differing from the literal wording of the provision regulating the issue in question. In has been thus concluded that a contract for the supply of agricultural produce should contain a provision allowing its cancellation rather than termination, but such a provision ought to be mandatory only in the case of fixed-term contracts, where the performance of the agricultural producer is continuous or periodical.